Uncovering the spatial link between environmental risks, diarrhea incidence, and health service accessibility - Listyono, Girlly Marchlina; Oinike, Adelina; Hambali, Dandi (Environmental and Materials, 2025)
Background: This study investigates spatial disparities between healthcare capacity, hospital accessibility, and environmental risk of diarrhea in West Java Province. Using a combination of Geographic Information System (GIS), network-based travel-time modeling, Principal Component Analysis (PCA), and clustering, the research identifies mismatches high-risk areas and low-access healthcare infrastructure. Spatial overlay reveals that districts such as Tasikmalaya, Garut, and Cianjur experience dual vulnerabilities—limited healthcare reach and elevated environmental risk indicators. Methods: PCA was used to reduce multicollinearity among six environmental and socioeconomic variables, including access to sanitation, drinking water, latrine type, and poverty level. After excluding three extreme outliers, 24 districts were clustered using PCA-derived composite scores. The clusters were overlaid with hospital accessibility maps from service area analyses (≤30 and 31–60 minutes). PCA explained 80.4% of the total variance. Findings: The results show that 3 out of 27 districts, such as Tasikmalaya, Garut, and Cianjur; exhibited critically low hospital bed ratios, and over 50% of their population is located outside the 30-minute service area of a hospital. PCA-based clustering revealed four spatial risk typologies, with Cluster 4 (extreme outliers) representing the highest composite risk from poor sanitation, communal latrines, and high poverty. These findings underscore a spatial mismatch between environmental vulnerability and healthcare accessibility. Conclusion: Integrated spatial planning is urgently needed in high-risk, low-access areas, combining infrastructure expansion with digital health solutions. Novelty/Originality of this article: This study introduces a spatial typology of diarrhea risk in West Java by integrating PCA and GIS-based accessibility, and aligns its recommendations with Indonesia’s national health policy frameworks (RPJMN 2025–2029 and PP No. 28/2024) to support data-driven, equitable public health interventions.